Data Analysis with a Wireless Multisensory Toxic Gas Detection System - Qiong Wu; Yunbo Shi (International Journal of Distributed Sensor Networks)
This paper proposes a wireless multisensory toxic gas detection system. The system allows remote wireless detection of four types of toxic gases, specifically Cl 2 , CO, NO 2 , and SO 2 , using gas detection technologies and wireless communication technologies such as ZigBee and Wi-Fi. Further, we analyze the data collected from sensors to determine a correspondence between the sensors and the gases and establish recognition models for different gases. Through multiple data calibration levels and industrial experiments, we have verified the feasibility of the system, along with its gas detection accuracy and long-term stability.